A prospective study to assess the efficacy of homoeopathic trituration of potassium sulphate on pityriasis capitis using seborrhea area and severity index - Kotian, Shreyank; Vidiera, Prennie (Indian Journal of Integrative Medicine, 2022)
Background: Pityriasis Capitis (Dandruff), is a highly prevalent dermatological disorder, effecting both the physical and the mental aspects of living. Hence, it becomes necessary to find out various methods to resolve the same. This study is focused to understand the effectiveness of homoeopathic remedy, Kalium sulphuricum in the treatment of Pityriasis Capitis. Methods: 15 Patients who have attended the outpatient unit of a private Homoeopathic Medical college Hospital were selected for the study. Patients of all the ages and both sexes were included in the study. The severity of spread and intensity of dandruff was calculated before and after the treatment using the Seborrhoea area and severity index (SSI) and the intensity of itching were measured pre and post using Pruritus numerical rating scale (PNRS). Result: 11 patients out of 15 i.e. 73.3% showed improvement in their symptoms of dandruff or itching and 26.7% of the individuals showed no marked improved. A mean decrease of 1.02 was seen in SASI scores before and after treatment. A mean decrease of 1.87 was seen in PNRS scores before and after treatment. Conclusion: This study shows that Kali sulphuricum has proved to be effective in the treatment of Pityriasis Capitis and has created the scope to investigate the need of external applications in the treatment of cases of dandruff.